2015
DOI: 10.1121/1.4926904
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the effects of masking on performance: The potential of multiple-voice masking in the office environment

Abstract: Broadband noise is often used as a masking sound to combat the negative consequences of background speech on performance in open-plan offices. As office workers generally dislike broadband noise, it is important to find alternatives that are more appreciated while being at least not less effective. The purpose of experiment 1 was to compare broadband noise with two alternatives—multiple voices and water waves—in the context of a serial short-term memory task. A single voice impaired memory in comparison with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
(70 reference statements)
1
25
0
Order By: Relevance
“…Attentional capture can also explain the fact that lowest number of pauses longer than 5 s was reached in the quiet conditions, as in quiet, there are no distracting sound elements. The results are in line with findings in Keus van de Poll et al () and Keus van de Poll et al (). The findings on workload are in line with the objective findings on writing fluency and number of pauses and support the idea that people do not appreciate environments with intelligible task‐irrelevant background speech.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Attentional capture can also explain the fact that lowest number of pauses longer than 5 s was reached in the quiet conditions, as in quiet, there are no distracting sound elements. The results are in line with findings in Keus van de Poll et al () and Keus van de Poll et al (). The findings on workload are in line with the objective findings on writing fluency and number of pauses and support the idea that people do not appreciate environments with intelligible task‐irrelevant background speech.…”
Section: Discussionsupporting
confidence: 93%
“…They found that writing fluency decreased as the intelligibility of the background speech signal increased. Keus van de Poll et al () explored this finding further and manipulated speech intelligibility by masking speech with other voices talking simultaneously (one voice masked with two, four, or six other simultaneous talking voices) instead of masking speech with pink noise. As more voices were talking simultaneously, speech intelligibility decreased.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the writing speed data and with our expectation, but, again, contrary to the results found in previous reports on the halfalogue effect (Emberson et al, ; Galván et al, ; Norman & Bennett, ). Although the writing speed data from both Experiments 1 and 2 only lent weak support for the assumption that background speech disrupts performance, several other studies have reliably shown that background speech disrupts writing (Keus van de Poll et al, , ; Sörqvist et al, ), and the subjective data suggest that background speech adds to experienced workload. In that sense, the subjective ratings and the performance data matched.…”
Section: Discussionmentioning
confidence: 81%
“…They found that the percentage of water features in the pictures was significantly correlated with improvements in the preference score between audio-only and audio-visual sessions. Because Haapakangas et al (2011) and Keus van de Poll et al (2015) supported WBMSs and the condition N1 involving a WBMS did not differ from condition P1a (pseudo-random masking sound) for every variable, it would be useful to investigate how the visual cues affect the perception of water sounds compared to the absence of visual cues.…”
Section: Discussionmentioning
confidence: 99%
“…Haapakangas et al (2011) found that a pouring water sound was a better speech masker with respect to acoustic satisfaction and cognitive performance than vocal music, instrumental music, pseudo-random noise or ventilation, although all of these sounds had exactly the same equivalent A-weighted SPL (45 dB) and spectrum slope (−5 dB per octave doubling). The cognitive and subjective benefits of a water sound have since been supported by Keus van de Poll et al (2015). …”
Section: Introductionmentioning
confidence: 92%